Positive Association between Individualism and Vaccination Resistance against COVID-19 Vaccination among Chinese Adults: Mediations via Perceived Personal and Societal Benefits - Yanqiu Yu (MDPI AG, 2021)
Background: Vaccination resistance is the key hurdle against herd immunity as it limits the final vaccination coverage. This study investigated the prevalence and factors of COVID-19 vaccination resistance (i.e., those indicating definitely not taking up COVID-19 vaccination), including individualism, perceived personal benefits (PPB) and perceived societal benefits (PSB) of COVID-19 vaccination, and related mechanisms of the association. Methods: A random telephone survey interviewed 395 unvaccinated adults aged 18–75 not having scheduled for COVID-19 vaccination in May 2021 in Hong Kong, China (response rate = 56.8%). Results: The prevalence of vaccination resistance was 56.5%. Adjusted for background factors, individualism, PPB, and PSB were significantly associated with vaccination resistance. Path analysis showed that individualism exhibited a direct effect on vaccination resistance and a 3-step indirect effect (individualism → PSB → PPB→ vaccination resistance) that explained 46.8% of the total effect. The two 2-step indirect paths via PPB only and via PSB only were non-significant. Conclusion: High prevalence of vaccination resistance was observed. Individualism increased vaccination resistance via its direct and indirect effects. Health promotion may emphasize collective good to reduce the impact of individualism and promote PPB/PSB, which may reduce vaccination resistance directly and alleviate the impact of individualism on vaccination resistance indirectly.